Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
a) 5xy + 9yz + 3zx + 5x - 4y
Step-by-step explanation:
→ (7xy + 5yz - 3zx) + (4yz + 9zx - 4y) + (-3xz + 5x - 2xy)
→ (7xy - 2xy) + (5yz + 4yz) + (-3zx + 9zx - 3xz) + (5x) + (-4y)
→ 5xy + 9yz + 3zx + 5x - 4y
Hence, option (a) is the correct answer.
Answer:
[tex]\textsf{A)}\quad \sf 5xy+9yz+3zx+5x-4y[/tex]
Step-by-step explanation:
Given expression:
[tex]\sf (7xy+5yz-3zx)+(4yz+9zx-4y)+(-3xz+5x-2xy)[/tex]
Remove the parentheses:
[tex]\implies \sf 7xy+5yz-3zx+4yz+9zx-4y-3xz+5x-2xy[/tex]
Collect like terms:
[tex]\implies \sf 7xy-2xy+5yz+4yz+9zx-3zx-3xz+5x-4y[/tex]
Combine like terms:
[tex]\implies \sf (7-2)xy+(5+4)yz+(9-3-3)zx+5x-4y[/tex]
[tex]\implies \sf 5xy+9yz+3zx+5x-4y[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.